Transnational coupling in the age of nation making during the 19th and 20th centuries - Leopoldie, Nicole (Anthem Press, 2023)
This work examines and compares courtship and marriage patterns that occurred between France and the United States during the nineteenth and twentieth centuries. Departing from state-centered studies of marriage law, it draws on the methodologies of transnational history, cultural history, and the history of emotion to show that these unions were part of a broader pattern of the larger cultural love affair between the two societies